In these last days: the dynamics of biblical revelation : biblical and systematic theology in the service of understanding Scripture - Goldsworthy, Graeme (Inter-Varsity Press, 2024)
Graeme Goldsworthy's magnum opus invites readers to reckon with the differing historical and cultural distances of texts from themselves when thinking about the application of the Scriptures.